Women's Employment in Tourism Sector in Turkey, Issues Faced, and the Effect of Glass Ceiling Syndrome on Women Workforce in Tourism - TEKELİ, HACER NEYİR (ASOS Eğitim Bilişim Danışmanlık Otomasyon Yayıncılık Reklam Sanayi ve Ticaret LTD ŞTİ., 2019)
After the Second World War, there has been a significant increasein the income of individuals worldwide. The increase in income hasproportionally brought about more work, tiring working conditions andthe fatigue of the working life. These factors along with ecologicalcomponents, employees’ need for rest, the spread of mass media, andthe advancement of technology have been influential in the developmentof tourism. As a matter of fact, these developments have been growingand growing every year. The number of tourists has increased everyyear giving rise to increased international tourism revenues. Tourismmovement on a world scale is in an ever increasing trend. According tothe data of the World Tourism Organization (UNWTO), 673 millionpeople participated in the tourism movement in 2000, while the saidparticipation increased to 1.046 million in 2010. According to theestimates of the same Organization, the number of people participatingin the tourism movement on a global scale will increase to 1.602 millionin 2020. In parallel with this mobility, it has been estimated thatapproximately 2 trillion dollars of international tourism income will begenerated in 2020 (www.unwto.org, 23.03.2011). The growth of tourismand the increase in the number of investments in tourism point to agrowing employment potential. The choice of seasonal employment inmany destinations of tourism offers opportunities especially for twogroups in terms of job opportunities; women and young people. The aimof this study was to focus on employment and especially femaleemployment in the tourism sector, which is an ever growing trend,called smokeless industry in economies of countries, and which is the star of service sector. Problems in female employment and especiallyglass ceiling syndrome have been examined through literature review.

İkinci Dünya Savaşından sonra dünya çapında bireylerin gelirinde gözle görülür bir artış olmuştur. Gelir artışı; buna bağlı orantıyla daha çok çalışmayı, çalışma şartlarının yoruculuğunu ve çalışma hayatının yorgunluğunu da beraberinde getirmiştir. Bu faktörler ve ekolojik unsurlar, kişinin dinlenme ihtiyacı hissetmesi, kitle iletişim araçlarının yaygınlaşması, teknolojinin ilerlemesi, turizmin gelişmesinde etkili olmuştur. Nitekim bu gelişmeler her yıl gitgide yükselen, büyüyen bir durum arz etmiştir. Her geçen yıl turist sayısı artmış; artan turist sayısı ise uluslararası turizm gelirlerinin büyümesine neden olmuştur. Dünya ölçeğinde turizm hareketi sürekli artan bir trenddedir. Dünya Turizm Örgütünün (WTO) verilerine göre 2000 yılında 673 milyon turist turizm hareketine katılırken, söz konusu katılım 2010 ‘da 1.046 milyona yükselmiştir. Örgütün tahminlerine göre, küresel ölçekte turizm hareketine katılan insan sayısı 2020 yılında 1.602 kişiye yükselecektir. Bu hareketliliğe paralel olarak, 2020 yılında yaklaşık 2 trilyon dolar uluslararası turizm geliri elde edileceği tahmini yapılmaktadır.( www.unwto.org, 23.03.2011) Turizmin gelişmesi ve turizme yapılan yatırımların sayısının çoğalması gittikçe büyüyen bir istihdam potansiyeline işaret etmektedir. Turizmin pek çok destinasyonunda mevsimsel istihdamın tercih edilmesi, iş imkânları bağlamında özellikle iki gruba fırsatlar sunmaktadır; Kadınlar ve gençler. Bu çalışmanın amacı; gittikçe büyüyen bir trend arz eden ve ülkelerin ekonomilerinde bacasız sanayi olarak adlandırılan, hizmet sektörünün yıldızı olan turizm sektöründe; istihdam ve özellikle kadın istihdamı üzerinde durulacaktır. Kadın istihdamında karşılaşılan sorunlar ve özellikle cam tavan sendromu literatür taraması ile incelenecektir.
Türki̇yede Turi̇zm Sektöründe Kadın İsti̇hdamı, Karşılan Sorunlar, Cam Tavan Sendromunun Turi̇zmde Çalışan Kadın İşgücüne Etkisi
Keywords: Female Employment in Tourism; Problems in Female Employment in Tourism; Glass Ceiling Syndrome